SOSIALISASI PENERAPAN DIGITALISASI APPOINTMENT DI RUMAH SAKIT AWAL BROS BATAM - Widya Putri; Riza Suci Ernaman Putri; Dinda Astya Monique (Transpublika Publisher, 2021)
Indirect registration is conducted online with the aim of reducing patient accumulation caused by lengthy registration times. The online registration system implemented by Awal Bros Hospital Batam offers four options: registration through the Haloawalbros application, Stardok, Chatbot (specifically for online registration via WhatsApp), and the Mobile JKN application for BPJS patients. This study aims to determine the procedures for the online appointment registration system at Awal Bros Hospital Batam. The research methodology includes population sampling techniques and operational definitions of research variables. Based on the research findings, Awal Bros Hospital Batam has successfully implemented an online appointment registration system. Four applications are available for conducting online appointments at Awal Bros Hospital Batam: Haloawalbros, Stardok, Chatbot with WhatsApp, and the Mobile JKN application for BPJS-insured patients.